2018
DOI: 10.1007/s12544-018-0285-9
|View full text |Cite
|
Sign up to set email alerts
|

SEM application to the household travel survey on weekends versus weekdays: the case of Seoul, South Korea

Abstract: Purpose This study analyzes the relationship that land use has with weekend travel in comparison to weekday travel. Unlike previous studies, it uses the same sample for two models that are specified to test the relationship separately for weekday and weekend travel. Methods Structural equation modeling is employed to test the land use-travel relationship. A comparison is made using two mode-specific travel measures: trip frequency and travel time.Results On weekday travel, land use in Seoul tends to reduce aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 63 publications
0
7
0
1
Order By: Relevance
“…Structural Equation Modeling (SEM) is a very powerful tool that it is increasingly used in travel behavior research [30][31][32][33][34][35]. In SEM, the relationships between theoretical constructs are represented by regression or path coefficients between the factors [36].…”
Section: Model Estimation and Resultsmentioning
confidence: 99%
“…Structural Equation Modeling (SEM) is a very powerful tool that it is increasingly used in travel behavior research [30][31][32][33][34][35]. In SEM, the relationships between theoretical constructs are represented by regression or path coefficients between the factors [36].…”
Section: Model Estimation and Resultsmentioning
confidence: 99%
“…specified as linear combinations of the observed variables ( Delbosc et al, 2020 , Golob, 2003 ). Additionally, SEM allows the assessment of highly collinear built environment variables in the same setting ( Gim, 2018 ). SEM can examine the distinctions between the total, direct, and indirect effects among the variables included in the analysis ( Chen and Akar, 2017 , Van Acker et al, 2007 ).…”
Section: Methodsmentioning
confidence: 99%
“…For modeling purposes (see Section 4), along with the time spent on each of the aforementioned activities and trips, the time spent on "other" activities that included any other types of daily activities, such as in-home activities without travel needs, was also computed by subtracting the total amount of time spent on mandatory and nonmandatory outdoor activities and associated trips, as well as daily sleep duration (assumed to be 7 hours a day) from the total daily time budget (24 × 60 = 1,440 minutes). Moreover, the date of the activity and trip-making (weekdays or weekends) was also included as an independent variable in this study, as many studies (Bhat & Misra, 1999;Schlich & Axhausen, 2003;Zhong et al, 2008;Gim, 2018;) have shown that individuals' activity-travel patterns for different purposes vary greatly between weekdays and weekends.…”
Section: Variables and Their Descriptive Statisticsmentioning
confidence: 99%